Awareness of human papillomavirus and its vaccine among patients attending primary care clinics at King Saud University Medical City - Maha F Alrajeh; Sulaiman Abdullah Alshammari (Wolters Kluwer Medknow Publications, 2020)
Objectives: We aimed to assess the awareness, attitudes, and practice regarding human papillomavirus (HPV) and its vaccine among women attending primary care clinics in Riyadh. Methods: This cross-sectional study included 326 women aged 18-60 years who attended primary care clinics between June 2014 and June 2015. The participants completed a validated, self-administered questionnaire. Data collected included sociodemographic information (e.g., age, marital status, education, and employment), knowledge of HPV and its vaccine, and attitudes regarding HPV vaccine acceptance. Results: Among the respondents, 59.4% were married, and 43.6% had received a university education. The study population had a marked lack of information regarding HPV infection and vaccination. Only 32.8% of the women knew that HPV is transmitted sexually, while 21% knew that it could cause cervical cancer. A quarter of the participants were aware of the protective vaccine against HPV. There were no statistically significant differences in participants' knowledge levels, according to age, marital status, educational level, and occupational status. The doctors, the media, and the friends were the primary sources of information to 5.6%, 7.7%, and 24.5% of the participants, respectively. Conclusion: Overall awareness of HPV and its vaccine and cervical cancer screening is low among Saudi women. There is a need for formulating preventive strategies and effective awareness programs for better HPV-related education, vaccine availability, and the importance of cervical cancer screening.